Young patients', parents', and survivors' communication preferences in paediatric oncology: Results of online focus groups - Kamps Willem A; Hoogerbrugge Peter M; van Dulmen Sandra; Tates Kiek; Zwaanswijk Marieke; Bensing Jozien M (BMC, 2007)
Abstract Background Guidelines in paediatric oncology encourage health care providers to share relevant information with young patients and parents to enable their active participation in decision making. It is not clear to what extent this mirrors patients' and parents' preferences. This study investigated communication preferences of childhood cancer patients, parents, and survivors of childhood cancer. Methods Communication preferences were examined by means of online focus groups. Seven patients (aged 8-17), 11 parents, and 18 survivors (aged 8-17 at diagnosis) participated. Recruitment took place by consecutive inclusion in two Dutch university oncological wards. Questions concerned preferences regarding interpersonal relationships, information exchange and participation in decision making. Results Participants expressed detailed and multi-faceted views regarding their needs and preferences in communication in paediatric oncology. They agreed on the importance of several interpersonal and informational aspects of communication, such as honesty, support, and the need to be fully informed. Participants generally preferred a collaborative role in medical decision making. Differences in views were found regarding the desirability of the patient's presence during consultations. Patients differed in their satisfaction with their parents' role as managers of the communication. Conclusion Young patients' preferences mainly concur with current guidelines of providing them with medical information and enabling their participation in medical decision making. Still, some variation in preferences was found, which faces health care providers with the task of balancing between the sometimes conflicting preferences of young cancer patients and their parents.